Case Study of the Relationship between Aqua Regia and Real Total Contents of Harmful Trace Elements in Some European Soils - Ričardas Taraškevičius; Rimantė Zinkutė; Rimutė Stakėnienė; Marijus Radavičius (Journal of Chemistry)
Both real total and aqua regia contents of trace elements in soils are often denominated by the same word “total” though the results are not identical. The formulas would be helpful for recalculation of aqua regia contents to real totals. Data for primary formulas were taken from the International Soil-Analytical Exchange Program of Wageningen Evaluating Programs for Analytical Laboratories. The degree of extractability DE of element in a sample was calculated by weighting the ratios of median contents in aqua regia to median real total contents in different periods with weights proportional to the respective number of determinations. According to descending median values of DE (%) in ISE European soil samples the elements are arranged as follows: Hg(98), Cd(94), Cu(91), Zn(90), Mn(89), Ni(88), Co(86), As(82), Mo(82), Pb(79), V(61), Sn(57), Cr(56), Sb(53), Be(51), B(46), U(35), and Ba(21). These values can be used for approximate recalculation of aqua regia contents to real totals and adjustment of contamination assessment. An attempt to obtain more explicit prediction by fitting regression models and problems related to high leverage and possibly influencial points are discussed and their possible relation to the specificity of soil composition is pointed out.